THE MEDIATING ROLE OF SOCIAL CAPITAL IN THE RELATIONSHIP BETWEEN FINANCIAL LITERACY AND FINANCIAL INCLUSION - Setiawan, Moh. Agung; Salim, Ubud; Khusniyah, Nur (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study is to examine the mediating role of social capital in the relationship between financial literacy and financial inclusion in the Malang Raya region. The unit of analysis used in this study is the people in Malang City, Malang Regency, and Batu City. The sampling technique used was proportionate stratified random sampling. Data analysis in this study used Partial Least Square (PLS). The results of this study indicate that financial literacy has a significant effect on financial inclusion. Financial literacy has a significant effect on social capital, social capital significantly affects financial inclusion, and social capital mediates the relationship between financial literacy and financial inclusion. This result shows that social capital has a partial mediating role, meaning that the effect on financial inclusion goes through the main predictor variable, financial literacy and social capital. Therefore, the local government can take advantage of policies related to social capital to impact efforts to improve financial inclusion in the community and regional economic conditions. This study also explained that, in general, the people in the Malang Raya region had good financial literacy. Future studies should use qualitative exploration by conducting interviews with respondents to explain other phenomena, especially for people geographically unbankable.